Isolation of amoxicillin-resistant oral streptococci from children and their mothers. Issue 1 (April 2015) - Nemoto, Hirotoshi; Nomura, Ryota; Nakano, Kazuhiko
Abstract: Background and objective: Infective endocarditis has been reported to be induced by invasive dental treatments in individuals with certain underlying heart disorders. Although oral amoxicillin (AMPC) is widely used for prophylaxis in the dental field, scant information is available regarding transmission of AMPC-resistant strains. In the present study, AMPC-resistant strains harbored in the oral cavities of children and their mothers were examined to consider the possibility of transmission between them. Design: AMPC-resistant strains were isolated from 320 saliva specimens taken from 150 healthy Japanese mother–child pairs using selective medium for streptococci containing AMPC. The minimum inhibitory concentrations of these strains were evaluated using a macrodilution broth method. Randomly amplified polymorphic DNA analysis was performed to compare the fingerprinting patterns of the strains. Results: AMPC-resistant streptococcal strains were isolated from 11 children and seven mothers, which included four mother–child pairs, although the fingerprinting patterns were consistent in only three. The proportion of children harboring AMPC-resistant strains with mothers who also harbored them was significantly higher than that of children whose mothers did not. Conclusion: Our results suggest that AMPC-resistant strains can be transmitted between mothers and their children.